FROM INSTITUTIONAL ACCREDITATION TO MONITORING OF EFFECTIVENESS - G. N. Motova; V. G. Navodnov (Высшее образование в России)
The article proposes a detailed analysis of the monitoring of higher education institutions effectiveness conducted annually by the Ministry of Education and Science for the last five years. The monitoring technique is based on collection and systematization of information used in state accreditation procedures in 1997–2010. The article also considers the reasons for implementing monitoring into the practice of governing body from the perspective of the state education policy. The list of HEIs’ performance indicators oriented mainly on social, economic and international policy, and the results of the follow-up procedures are criticized by the academic community. The authors propose a model of presentation the monitoring results in the League Tables format. It helps using the monitoring results in a flexible manner both by institutions of higher education management and by HEIs aimed at analyzing their policies and forming their development strategies. This paper is especially relevant in the framework of one more round of university effectiveness monitoring to be conducted in 2018. In conclusion, the conducted effectiveness monitoring can reflect the current situation of the education system on conditions of transparency of set goals and stability of “game rules”. But this instrument does not give universities the possibility of strategic and tactical vision of further development due to the limitation by the binary scale of decision-making. The given method of university clustering in league tables according to monitoring data may help universities develop a strategy of improving the quality of their activity.